Визначення перехідного опору і показника розрядження окремого насіння - Чебанов, Андрій Борисович; Чебанов, Андрей Борисович; Chebanov, Andrii; Чебанова, Юлія Василівна; Чебанова, Юлия Васильевна; Chebanova, Yuliia (My University, 2019)
UK: Робота присвячена питанню розділення зернової суміші за її фізико-механічними і електричними властивостями. Наведено методику визначення перехідного опору і показника розрядження окремого насіння, значення яких чинять вплив при розділенні зернових сумішей на барабанних електросепараторах. На прикладі пшениці встановлено, що зі збільшенням напруги поля опір зерен зменшується, причому у більш вологих зерен швидше, ніж у менш вологих. Визначення величин перехідного електричного опору різного насіння значно допоможе вплинути на процес електросепарації на барабанних електросепараторах. RU: Работа посвящена вопросу разделения зерновой смеси по ее физико-механическим и электрическим свойствам. Приведена методика определения переходного сопротивления и показателя разряжения отдельного зерна, значения которых оказывают влияние при разделении зерновых смесей на барабанных электросепараторах. На примере пшеницы установлено, что с увеличением напряженности поля, сопротивление зерен уменьшается, причем в более влажных зернах быстрее, чем в менее влажных. Определение величин переходного сопротивления различных семян значительно поможет повлиять на процесс электросепарации на барабанных электросепараторах. EN: The increase of the productivity and cost cutting in the process of production of grain-crops up to a point depend on quality of sowing material, and accordingly, and from the method of his cleaning and sorting. One of effective methods of division of grain mixtures there is an electro-separation. It is set that after the row of certain advantages, by the widespread type of electrical-separators drum, in that there is grain mixture, that acted on the surface of the rotary-type earthed electrode-drum gets a charge from a crowning electrode to the drum and under operating of forces of the field, forces of cooperation of the charged particle under flat of drum, centrifugal forces and attractive powers there is a division of mixture. For that, to learn behavior of grains on a cylindrical electrode (drum) that runs around and their distribution in the field of native digit, it is necessary to know character of change of resistance of every separately taken seed in his natural state. In agricultural practice the bulk of seed clears up in a collective period - for this period characteristic considerable oscillation of humidity of environment that affects humidity of seed. In a period cleaning and sorting of sowing material there are considerable fluctuations in an ambient temperature. In this connection it is necessary to know how transitional resistance of seed changes with the change of his humidity and temperature. Methodology over of determination of transitional resistance and index is in-process brought discharging of separate seed, the values of that have influence at dividing of grain mixtures into drum electrical separators. On the example of wheat, it is found that with increasing field strength, the resistance of grains decreases, and in wetter grains faster than in less wet ones. The determination of the values of the transition resistance of different seed will greatly help to influence the process of electroseparation on a drum electroseparation.
Определение переходного сопротивления и показателя разрядки отдельного зерна
Determination of transient resistance and rate of discharge of the individual grains
Keywords: зернова культура; електросепарація; барабанна машина; напруженість поля; критерій розділення; міжелектродна відстань; зерновая культура; электросепарация; барабанная машина; напряженность поля; критерий разделения; межэлектродное расстояние; grain culture; electroseparation; drum machine; field strength; separation criterion; electrode distance